Agricultural insurance and rural revitalization—an empirical analysis based on China’s provincial panel data - Zhou, Chao; Liu, Jia; Wan, Shenwei; Zheng, Hongling; Chen, Song (Frontiers in Public Health, 2023)
Agricultural insurance is a kind of compensation insurance designed to provide protection for the economic losses caused by insured accidents suffered by agricultural producers in agricultural production. Rural revitalization refers to the strategy of improving the level of rural economic, social and cultural development and achieving coordinated and sustainable development of urban and rural development. Agricultural insurance can effectively diversify risks and reduce losses for agricultural producers, which plays an important role in stabilizing farmers’ income, helping rural economic development, and promoting rural revitalization. Based on the theoretical analysis of the mechanism of agricultural insurance on rural revitalization, this paper empirically studies the effect of agricultural insurance on rural revitalization by using panel data from various provinces in China from 2011 to 2020.1 In this paper, the TOPSIS entropy weight method, the system generalized method of moments (GMM) and the threshold model are used to calculate the actual development level of rural revitalization in each province of China, the promotion effect of agricultural insurance on the development level of rural revitalization and the promotion of rural revitalization in five dimensions, and whether there is a threshold effect of agricultural insurance on rural revitalization. The empirical results show that: (1) The level of rural revitalization in various provinces in China shows a dynamic trend of “overall slow rise, with obvious differences between provinces.” (2) Improving the development level of agricultural insurance can drive the improvement of China’s rural revitalization level, and every 1 unit increase in the development level of agricultural insurance will drive the level of China’s rural revitalization to increase by 0.1633 units. At the same time, the role of agricultural insurance on social etiquette and civility is not significant, and the role of the remaining four rural revitalization goals is significant. (3) Agricultural insurance has a significant effect on the level of rural revitalization in eastern provinces, but does not play a significant role in rural revitalization in central and western provinces. (4) The role of agricultural insurance on rural revitalization has a double threshold effect. Accordingly, this paper puts forward some suggestions for increasing the capital investment in agricultural insurance, innovating the new mode of agricultural insurance operation, promoting the in-depth development of agricultural insurance according to local conditions, and reasonably adjusting the capital investment of agricultural insurance. Finally, because the data used in this paper do not cover the entire process of rural revitalization and the research is mainly carried out from a macro perspective, there are still some shortcomings in this paper.